Analysis Study of Remedial Activity Implementation in The Learning Process in Elementary Schools - Vivi Darmayanti; Nora Sara Damayanti; Yuli Nurmalasari (STEAM Journal For Elementary School Education, 2025)
This study aims to analyze the implementation of remedial activities in the learning process in elementary schools. The background of this study is based on the fact that not all students are able to achieve learning completion simultaneously due to individual differences, learning styles, and environmental conditions. Remedial programs are seen as an important strategy to overcome students' lag in mastering subject matter. This study uses a descriptive qualitative approach with a questionnaire instrument distributed to 78 teachers from various elementary schools in Indonesia. The results of the study showed that the type of remedial activity most often used was reteaching the material, with a percentage of 72%. Other activities include group work, use of teaching aids, tutorials with peers, and reading relevant learning resources, with a lower frequency. Factors that influence the effectiveness of remedial activities include teacher readiness, student characteristics, limited facilities, and low student reading interest. These findings indicate that teachers tend to choose a remedial approach that is direct and interaction-based, while activities that require independent learning are still rarely used. This study recommends increasing teacher capacity in designing remedial strategies that are varied and according to student needs, as well as providing learning facilities that support effective remedial learning.